The distribution of MNS hybrid glycophorins with Mur antigen expression in Chinese donors including identification of a novel GYP.Bun allele. Issue 3 (27th May 2016) - Wei, L.; Shan, Z. G.; Flower, R. L.; Wang, Z.; Wen, J. Z.; Luo, G. P.; Ji, Y. L.
Abstract : Background and Objectives: MNS hybrid glycophorins are identified by characteristic antigen profiles. One of these is the Mur antigen, which is expressed on red cell hybrid glycophorins of several phenotypes of the 'Miltenberger' series found predominantly in East Asian population. The aim of this study was to investigate the distribution of Mur‐positive hybrid glycophorins and clarify the genetic basis in the donors from southern China. Materials and Methods: Blood samples from 528 donors were collected for Mur antigen serological typing. Sequencing of GYPB pseudoexon 3 and MNS phenotyping were conducted in Mur‐positive samples. The multiplex ligation‐dependent probe amplification (MLPA) was used to confirm the zygosity of the GYP.Mur allele and determine the MNSs genotype. The expression of Mur antigen was evaluated by flow cytometry. Results: Fifty‐one Mur‐positive samples were identified by serological testing. Sequencing analysis showed 50 donors (50/528, 9.5%) with the GYP . Mur allele (48 heterozygotes and two homozygotes), which were confirmed by the MLPA genotyping analysis, and one donor (1/528, 0.19%) with a novel GYP.Bun allele. Flow cytometry analysis revealed higher Mur antigen expression on GP.Mur (Mi.III) homozygotes than heterozygotes. For the GYP.Mur homozygotes, an incorrect 'N' positive typing with anti‐N lectin was obtained. Conclusion: GP.Mur (Mi.III) is the main Mur‐positive hybrid glycophorin in Guangzhou donors. The dosage effect of Mur antigen observed provides a basis for selecting the homozygous GP.Mur RBCs as the reagent cells to avoid neglecting weak antibodies. A separate GYP.Bun lineage found in the southern China provides evidence for further complexity in the MNS system.